2019
DOI: 10.5089/9781513512488.001
|View full text |Cite
|
Sign up to set email alerts
|

Financial Repression is Knocking at the Door, Again

Abstract: Financial repression (legal restrictions on interest rates, credit allocation, capital movements, and other financial operations) was widely used in the past but was largely abandoned in the liberalization wave of the 1990s, as widespread support for interventionist policies gave way to a renewed conception of government as an impartial referee. Financial repression has come back on the agenda with the surge in public debt in the wake of the Global Financial Crisis, and some countries have reintroduced adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 59 publications
0
11
0
1
Order By: Relevance
“…as ceilings on interest rates, directed credits to certain industries, or constraints on the composition of bank portfolios, financial repression is typically accompanied by additional restrictions on financial activity (Jafarov et al 2020).…”
mentioning
confidence: 99%
“…as ceilings on interest rates, directed credits to certain industries, or constraints on the composition of bank portfolios, financial repression is typically accompanied by additional restrictions on financial activity (Jafarov et al 2020).…”
mentioning
confidence: 99%
“…These theoretical arguments have been tested by numerous empirical studies. Many studies have confirmed a negative association between interest rate repression and several macroeconomic outcomes such as savings rates, investment and economic growth (Fry, 1978(Fry, , 1997Roubini and Sala-i-Martin, 1992;Jafarov et al, 2019). Interest rate repression has also been found to be harmful to financial development.…”
Section: >>>mentioning
confidence: 97%
“…However, existing studies either take a narrow geographical perspective, focusing on EMDEs (Helms and Reille, 2004) or advanced economies (see Reifner et al, 2010, for the EU; and Dasgupta and Mason, 2019, for the US), or, when taking a global perspective, they focus on lending interest rate caps only (Maimbo and Gallegos, 2014;Ferrari et al, 2018). In a paper similar to ours, Jafarov et al (2019) attempt to compile a database on all types of IRCs and construct a basic index (i.e. based on binary variables) of IRCs across economies.…”
Section: > > > B O X 1 Ircs In the Time Of Covid-19mentioning
confidence: 99%
“…These theoretical arguments have been tested by numerous empirical studies. Many studies have confirmed a negative association between interest rate repression and several macroeconomic outcomes such as savings rates, investment and economic growth (Fry, 1978(Fry, , 1997Roubini and Sala-i-Martin, 1992;Jafarov et al, 2019). Interest rate repression has also been found to be harmful to financial development.…”
Section: Introductionmentioning
confidence: 97%
“…However, existing studies either take a narrow geographical perspective, focusing on EMDEs (Helms and Reille, 2004) or advanced economies (see Reifner et al, 2010, for the EU;and Dasgupta and Mason, 2019, for the US), or, when taking a global perspective, they focus on lending interest rate caps only (Maimbo and Gallegos, 2014;Ferrari et al, 2018). In a paper similar to ours, Jafarov et al (2019) attempt to compile a database on all types of IRCs and construct a basic index (i.e. based on binary variables) of IRCs across economies.…”
Section: Introductionmentioning
confidence: 99%